2017
DOI: 10.1007/s11274-017-2217-6
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic molecular diversity at different steps of the wastewater treatment plant process reveals more phylogenetic novel lineages

Abstract: Wastewater microbiota represents important actors of organic depollution. Nowadays, some species used as bioindicators of the effluent quality are still identified by microscopy. In the present study, we investigated eukaryotic diversity at the different steps of the treatment process of a wastewater treatment plant (aerobic, anaerobic, clarifier basins and anaerobic digester) using the 18S rRNA gene sequencing approach. Of the 1519 analysed sequences, we identified 160 operational taxonomic units. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…99 ). A multitude of recent studies confirmed next to fermentative yeasts a dominance of "dark matter fungi" (mainly Rozellomycota), often in the anaerobic, biofilm dominated stages [100][101][102][103][104] . Their function in wastewater processing is unclear, and it will be highly interesting, if "dark matter fungi" have the same potential for biotechnologies than higher fungi (e.g.…”
Section: Artificial Habitatsmentioning
confidence: 99%
“…99 ). A multitude of recent studies confirmed next to fermentative yeasts a dominance of "dark matter fungi" (mainly Rozellomycota), often in the anaerobic, biofilm dominated stages [100][101][102][103][104] . Their function in wastewater processing is unclear, and it will be highly interesting, if "dark matter fungi" have the same potential for biotechnologies than higher fungi (e.g.…”
Section: Artificial Habitatsmentioning
confidence: 99%
“…Species within the Parcubacteria appear to be obligate anaerobe and likely live in symbiosis with a wide range of other prokaryotic or eukaryotic members of the community (Nelson and Stegen, 2015). Particularly, one taxon was observed as an endoplasmic symbiont of a freeliving Ciliophora (Gong et al, 2014), which can represent a dominant fraction of the eukaryotic microbial community in WWTPs (Chouari et al, 2017;Matsunaga et al, 2014). The detection of positive-responder OTUs related to protozoan-associated bacteria could indicate that symbiotic associations within wastewater systems might be much more prevalent than currently thought, and that the presence of TBBPA might stimulate the establishment of such symbiotic relationships within the community.…”
Section: Microbial Community Taxonomic Compositionmentioning
confidence: 99%
“…To this end, we borrowed the idea of Shannon's metric of information entropy (Shannon 2001) (Shannon index), which quantifies the uncertainty in predicting the identity of a randomly chosen entity from a system. Shannon index is frequently used in ecology as an index for species diversity (the uncertainty of predicting the species randomly captured from a community) (Tuomisto 2010), or similarly for measuring molecular diversity in various biological systems (the uncertainty of predicting the sequence randomly picked from a pool of nucleic acid or protein) (Lin 1996;Medinger, et al 2010;Chouari, et al 2017;Mangin, et al 2017), or RNA folding specificity as defined by the computationally predicted ensemble of secondary structures (Huynen, et al 1997). Adapted from Shannon entropy, we measured the diversity of folding by obs = − ∑ , , ln , .…”
Section: Estimation Of Folding Specificity For Mrnamentioning
confidence: 99%